PENTINGNYA PERSEPSI GENERASI Z DI KOTA SALATIGA TERHADAP INTEGRITAS DAN SIKAP ANTI KORUPSI - Tunjung Wijanarka; Daru Purnomo; Kris Julis Iman Murni Waruwu; Rr. Sri Rejeki Anggraeni Kartodinoto (Universitas Halu Oleo (UHO), 2024)
This paper tries to describe the issue of corruption which is still one of the latent and systemic problems for the Indonesian nation. Proven by corruption, many losses ultimately have an impact on society at large. Democracy has proven to be incapable of overcoming the problem. The democratic concept of limiting power and the role of the people as the highest ruler does not really make Indonesia, which is a democratic country, free from corruption cases. In fact, perpetrators of corruption crimes in Indonesia are dominated by those who have higher education. This picture shows that high education is not directly proportional to integrity and anti-corruption attitudes. Therefore, this study seeks to examine the importance of perceptions of integrity and anti-corruption attitudes among Generation Z in Salatiga City as the nation's successors in the future. Through descriptive quantitative research methods, the author obtained research results that Generation Z in Salatiga City has a good perception of anti-corruption attitudes which can be the basis for avoiding corrupt practices. Thus, the author concludes that the perception of integrity and anti-corruption culture has an important role in building and preventing attitudes that lead to corruption, especially among Generation Z in Salatiga City.